UV-induced tetrazole-thiol reaction for polymer conjugation and surface functionalization - Feng, Wenqian; Li, Linxian; Yang, Chengwu; Welle, Alexander; Trapp, Oliver; Levkin, Pavel A. (Angewandte Chemie. International edition, 2015)
A UV-induced 1,3-dipolar nucleophilic addition of tetrazoles to thiols is described. Under UV irradiation the reaction proceeds rapidly at room temperature, with high yields, without a catalyst, and in both polar protic and aprotic solvents, including water. This UV-induced tetrazole-thiol reaction was successfully applied for the synthesis of small molecules, protein modification, and rapid and facile polymer-polymer conjugation. The reaction has also been demonstrated for the formation of micropatterns by site-selective surface functionalization. Superhydrophobic-hydrophilic micropatterns were successfully created by sequential modifications of a tetrazole-modified porous polymer surface with hydrophobic and hydrophilic thiols. A biotin-functionalized surface could be fabricated in aqueous solutions under long-wavelength UV irradiation.